Industry 4.0 competencies among lecturers of higher learning institution in Malaysia - Tan Owee Kowang; Mohamad Fawzy Bakry; Ong Choon Hee; Goh Chin Fei; Lim Kim Yew; Mohd Saiful Izwaan Saadon; Choi Sang Long (International Journal of Evaluation and Research in Education (IJERE), 2020)
Industry 4.0 is a new breed from the past industry revolution. The revolution implies an inevitable impact on professional sectors, including education field. Higher Learning Institution (HLI) is viewed as the platform for the development of Industry 4.0 competencies. However, research related to Industry 4.0 competencies among educators or academicians is scarce. Hence, this study aims to assess the level of Industry 4.0 competencies among lecturers in one of higher learning institution in Malaysia, as well as to identify Industry 4.0 competencies that required further enhancement. Five Industry 4.0 competencies identified from literature review, which are Information and Communication Technologies (ICT), Organizational Learning, Innovative Management, Environment and Continuous Improvement competencies. The importance level and implementation level perceived by the lecturers across the five competencies are assessed via questionnaire which responded by 132 lecturers from a higher learning institution in Malaysia. Data collected is analyzed via descriptive analysis to assess the importance and implementation levels perceived by the respondent. In addition, an improvement opportunity index, namely Focus Index is calculated for each competency. Finding from the study reveals that all the four Industry 4.0 competencies are perceived by respondents as important, however implemented at moderate level. Analysis result of Focus Index also suggests that competencies in term of Organizational Learning and ICT are “over focus”, while Environment competency is viewed as “under focus” which required further enhancement.